Spatial trade-offs in national landbased wind power production in times of biodiversity and climate crises - Kristine M. Grimsrud; Cathrine Hagem; Kristina Haaskjold; Henrik Lindhjem; Megan Nowell (Statistics Norway, Research Department, 2022)
Energy generated from land-based wind power is expected to play a crucial role in the decarbonisation of the economy. With the looming biodiversity and nature crises, spatial allocation of wind power cannot, however, any longer be considered solely a trade-off against local disamenity costs. Emphasis should also be put on wider environmental impacts, especially if these challenge the sustainability of the whole renewable energy transition. We suggest a modelling system for spatial allocation of wind power plants (WPPs) by combining an energy system model with a comprehensive GIS analysis of WPP sites and surrounding viewscapes. The modelling approach integrates monetary cost estimates of local disamenity and loss of carbon sequestration, and impacts on wilderness and biodiversity implemented as sustainability constraints on the model. Simulating scenarios for the Norwegian energy system towards 2050, we find that the southern part of Norway is the most favourable region for wind power siting when only the energy system surplus is considered. However, when gradually adding local disamenity costs (and to a lesser extent carbon costs) and the sustainability constraints, the more beneficial siting in the northern part of Norway become. We find that the sustainability constraints have the largest impact on the spatial distribution of WPPs, but the monetised costs of satisfying them are shown to be modest. Overall, results show that there is a trade-off between local disamenities and loss of biodiversity and wilderness. Siting wind power plants outside the visual proximity of households yield negative consequences for biodiversity and wilderness.
Keywords: C61; D62; Q24; Q42; Q48; Q51; Q57; Q58; 330; wind power; spatial analysis; energy system model; environmental costs; disamenity costs